Impact of A1 segment asymmetry on hemodynamic conditions around the circle of Willis and anterior communicating artery aneurysm formation - Lee, Joonho; Jeong, Seul-Ki; Hong, Ji Man (Frontiers in Neurology, 2025)
BackgroundThis study aims to investigate how A1 segment asymmetry—also known as A1 dominancy—influences the development of the anterior communicating artery aneurysm (AcomA) as it affects hemodynamic conditions within the circle of Willis (COW). Using time-of-flight magnetic resonance angiography (TOF-MRA), the research introduces a novel approach to assessing shear stress in A1 segments to uncover the hemodynamic factors contributing to AcomA formation.MethodAn observational study was conducted over 6 years at a tertiary university hospital’s outpatient clinic. Recruited patients who underwent TOF-MRA imaging were divided into AcomA and non-AcomA groups. MRA images were analyzed using semi-automatic software (VINT, Mediimg, Inc.) to calculate the signal intensity gradient (SIG), which reflects wall shear stress. The comparison metrics included general demographics, anatomical characteristics, and hemodynamic attributes of the COW, mainly focusing on A1 segment asymmetry.ResultsAmong the 700 subjects, 106 were categorized into the AcomA group, while 594 were placed in the non-AcomA group. The AcomA group showed a more significant difference in the bilateral A1 diameter (49.0% vs. 20.8%, p < 0.001) and a greater prevalence of unilateral A1 aplasia (32.1% vs. 6.7%, p < 0.001) compared to the non-AcomA group. Increased bilateral A1 asymmetry in the AcomA group corresponded with notable variations in A1 SIG, indicating increased wall shear stress. The occurrence of AcomA is associated with both anatomical factors of the circle of Willis, represented by the bilateral A1 diameter ratio, and hemodynamic factors, represented by the bilateral A1 SIG ratio, suggesting that both factors are almost equally significant.ConclusionOur findings suggest that A1 segment asymmetry influences hemodynamic changes within the COW, contributing to AcomA formation. Hemodynamic factors provide an intuitive understanding of how anatomical characteristics within the COW can lead to aneurysm development.